Effect of hCG and prostaglandin on ovarian, luteal development, and hormonal changes in embryo donor mares during the hot summer months in subtropics - Jamal Mohamed Hassan Alkhadrawy; Amal Mahmoud Aboelmaaty; Mostafa Mohamed Abou-Ahmed; Abdelraouf Morsy Ghallab (Open Veterinary Journal)
Background: Commercial embryo flushing of horses has required hormonal management of both the donor and recipient mares throughout the breeding season. Aim: This study aimed to find out the effect of using human chorionic gonadotropin (hCG) and prostaglandin F2α (PG) on the ovarian and uterine dynamics and hemodynamics, estradiol, progesterone, oxidants-antioxidants, and blood biochemicals in embryo donor mares during the hottest months of the year in a subtropical climate. Methods: Three Control estrous cycles of native mares (10-20 years; N=10) followed by two treated cycles with hCG and PGF2α were examined daily from May to August using Doppler ultrasound with blood sampling. Circulating estradiol (E2), progesterone (P4), total cholesterol, total proteins, albumin, haptoglobin, nitric oxide (NO), catalase, alkaline phosphatase, lactate dehydrogenase (LDH), and myeloperoxidase were measured in blood serum. Results: Days during the control estrous cycle impacted the dominant follicle (DF) diameter (P [Open Vet J 2024; 14(8.000): 2057-2072]